KEMAMPUAN KANJI MAHASISWA TINGKAT III PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TAHUN AJARAN 2013/2014 - Iis Wijayanti; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research explain about Japanese Education Major Riau University third years students kanji skill. The purpose of this research is to know what kind of kanji’s skill student find difficult to understand. There are 12 kinds of kanji skill that being tested to students,  the 12 kinds of skills are: Reading , word structure, shape (bushu), writing (simple words), writing (complicated words), choice from the context, usage (word kinds), usage (okurigana) reading from the context, reading  (simple words), reading (complicated words), ON reading.The result show that, between these 12 kanji skills that being tested only two skill got B grade those are shape skill with 70,8% and usage (okurigana) with 71,7%. Key Words: kanji skill, reading, writing,  shape